Multipurpose grinder for the grinding of cereals, rice husk and other dry agricultural residues in Sub Sahara Africa - CGIAR Research Program on Rice (2021)
The components of the technology have been fabricated, tested and validated with key stakeholders in Benin. Piloting has been carried out with actors in Benin and Cote d'Ivoire. Technical drawings of the equipment have been prepared and publicly available.